Euro-austerity and welfare states : comparative political economy of reform during the Maastricht decade - Bolukbasi, H. Tolga (European Union studies., 2021)
"Euro-Austerity and Welfare States analyses the political economy of welfare state reform in the first episode of Euro-austerity during the 1990s. It shows how Europe's welfare states survived unrelenting pressures stemming from the Economic and Monetary Union (EMU) laid out in the Maastricht Treaty of 1992. Throughout, H. Tolga Bolukbasi draws lessons for scholars and policy practitioners, and his insightful analysis sheds important light on the second wave of Euro-austerity that set in following the Great Recession of 2008. Paying careful attention to government expenditures and budgetary politics, Bolukbasi analyses the political economy of reform in countries where the EMU's impact was expected to be greatest. Based on in-depth comparative case studies of Belgium, Greece, and Italy, he shows how scholars, policymakers, and citizens alike expected Euro-austerity to erode Europe's welfare states. Contrary to popular opinion, Bolukbasi finds that the reality was much more complicated. A thorough critique of the "Euro-austerity hypothesis," this book presents a rigorous comparative study of the resilience of the welfare state in various national contexts."--